2005
DOI: 10.1002/jor.20031
|View full text |Cite
|
Sign up to set email alerts
|

Delay of supraspinatus repair by up to 12 weeks does not impair enthesis formation: A quantitative histologic study in rabbits

Abstract: The purpose of this study was to find out whether supraspinatus repair delayed by up to12 weeks affects the formation of a new enthesis when compared to an immediate repair. In 67 rabbits, the supraspinatus fibrocartilaginous enthesis of one shoulder was resected. The tendon was attached to the greater tuberosity either immediately, after a 6-week, or after a 12-week delay. Five histologic variables were used to assess enthesis formation: number of non-chondrocytes, number of chondrocytes, alignment of chondro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 44 publications
2
44
0
2
Order By: Relevance
“…They repeated this study with the same method but delayed repair to either 6 or 12 weeks after rotator cuff injury. 16 They showed that although this delay in repair did not have an effect on enthesis formation, the formation of this fibrocartilaginous structure was dependent on the time elapsed after repair. These studies on the normal enthesis formation after surgical repair of the rotator cuff are critical as we move forward to determine better ways to improve healing.…”
Section: Tendon-to-bone Enthesismentioning
confidence: 97%
“…They repeated this study with the same method but delayed repair to either 6 or 12 weeks after rotator cuff injury. 16 They showed that although this delay in repair did not have an effect on enthesis formation, the formation of this fibrocartilaginous structure was dependent on the time elapsed after repair. These studies on the normal enthesis formation after surgical repair of the rotator cuff are critical as we move forward to determine better ways to improve healing.…”
Section: Tendon-to-bone Enthesismentioning
confidence: 97%
“…Image J (National Institutes of Health, Bethesda, MD, USA) software was used to determine the area of new fibrocartilage formation by manually outlining the metachromasia at the tendon-bone repair site on the safranin-O-stained slides at a total magnification of 9 40 on three sequential coronal sections. Total area of metachromasia was recorded for each specimen as squared micrometers and the mean ± SD for each group was determined [19].…”
Section: Histologic Analysismentioning
confidence: 99%
“…The total area of metachromasia was recorded for each specimen. 23 Using polarized light microscopy, 2-week and 4-week tissue sections were stained with picrosirius red for semiquantitative analysis of collagen fiber alignment and organization at the repair site. By quantifying the collagen birefringence under polarized light, differences in collagen deposition and maturation in the healing tendon could be detected.…”
Section: Histomorphometric Analysis and Immunohistochemical Localizationmentioning
confidence: 99%